AVALIAÇÃO DA SATISFAÇÃO DO USUÁRIO DO PMCMV SOB O ENFOQUE DO CONFORTO AMBIENTAL - Berleze, Angélica; Silvoso, Marcos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This short paper is the result of a research carried out in a low-income housing complex in the city of Chapecó/SC, which aims, through a post-occupancy evaluation, to evaluate user satisfaction regarding the environmental comfort of single-family buildings. For that, a multimethod approach was used. It was consisted of quantitative and qualitative methods such as walkthrough, questionnaire and focus group analysis. The results showed low residents' satisfaction with temperature and humidity aspects in some dwelling environments and a greater need for passive conditioning of this building due to the low capacity in use of artificial systems.